The dynamic change of oolong tea constitutes during enzymatic‐catalysed process of manufacturing. (13th July 2020) - Huang, Xujian; Cao, Hongli; Guo, Yaling; Liu, Jianghong; Sun, Yun; Liu, Shengrui; Lin, Jinke; Wei, Shu; Wu, Liangyu
Summary: To understand leaf enzyme‐modulated dynamic changes of character constitutes during withering and turning‐over steps of oolong tea manufacturing, complementary proteomic and metabolomic analyses were performed using the processed tea leaves from the two steps. A total of 778 metabolites and 6274 proteins were identified and quantified in this study. A biosynthetic pathway network of flavouring compounds was suggested in combination with the abundance of candidate enzymes. The free amino acids were necessary not only to the umami or sweet tastes of oolong tea, but also to the biosynthesis of secondary metabolites responsible for the environmental stress. As the downstream derivatives of the phenylpropanoid pathway with phenylalanine as one of the upstream metabolites, the glycosides of isoflavonoids and anthocyanins showed decreasing trends during the enzymatic‐catalysed process, potentially contributing to flavour of mellow and brisk. The formation of flavouring compounds in oolong tea production is a result of systematic responses to serious stress conditions, during which a series of defensing mechanisms in tea leaves were triggered to induce dynamic changes in various enzymes and metabolites. Abstract : The metabolism pathways during oolong tea enzymatic‐catalyzed process.